CREATIVE WORK SERIES: WARMTH THE PROCESS OF CREATING WORKS USING MIXED MATERIAL METHODS TO PRESENT A PARADIGM WITHIN THE FAMILY CONTEXT - PHIMTHEP, CHALOEMPHONG (Journal of Suan Sunandha Arts and Culture, 2024)
“Warmth” creative works in the form of mixed materials Born from the inspiration from the influence of love and relationship under the farming family. based on the concept of creating a memorial to go back in time and revisiting memories through taking into account family members in the familiar way of life To maintain the cycle through the agricultural way of life from the creator's personal experience, which is a paradigm under the family context. using the theory of creativity through the process of mixed media visual arts There are relics from the relationship, which are objects, utensils from the traces of his father's occupation. Mother's garments, as well as the vegetation of the Creator's homeland. arranged and merged into images from the concept of portraits, stories, contents of memories Come out in the form of creative works in the field of visual arts. Achievement and body of knowledge that resulted in 3 creative works and a reflection of the essence of love and warmth in the relationship area. in the space of imagination